BERBAGI DALAM KASIH DAN SUKACITA DI RUMAH RUTH - Yulia Jayanti Tanama; Agnes Monica Halawa; Victor Deak (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
Rampant promiscuity of adolescents has resulted in many cases of abortion; based on data, Indonesia ranks 4th in the world. The family plays an essential part in influencing their children's lives spiritually, sexually, socially, and in achievement. Parents should teach their children to read the Bible, pray, and worship early. Parents are also responsible for teaching sexual education and educating children to realize that their body is the temple of God. Teenagers who have already fallen into free sex, causing unwanted pregnancies, need counselling, assistance, and faith strengthening. Rumah RUTH stands to answer the needs of pregnant teenagers out of wedlock, women who experience sexual violence, children who have an abortion, and children who are neglected. The purpose of this research is to share love and joy with the children at Rumah RUTH.